2020
DOI: 10.3390/ijms21228855
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs in Ovarian Cancer Progression, Metastasis, and Main Pathways: ceRNA and Alternative Mechanisms

Abstract: Ovarian cancer (OvCa) develops asymptomatically until it reaches the advanced stages with metastasis, chemoresistance, and poor prognosis. Our review focuses on the analysis of regulatory long non-coding RNAs (lncRNAs) competing with protein-coding mRNAs for binding to miRNAs according to the model of competitive endogenous RNA (ceRNA) in OvCa. Analysis of publications showed that most lncRNAs acting as ceRNAs participate in OvCa progression: migration, invasion, epithelial-mesenchymal transition (EMT), and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 223 publications
2
103
0
Order By: Relevance
“…In terms of the working mechanism, lncRNAs can compete for miRNAs through the same miRNA recognition element, which lowers the negative regulatory actions of miRNAs on target genes and indirectly modulates target mRNA levels (33). To investigate whether USP30-AS1 acts as a miRNA sponge, the exact distribution of USP30-AS1 in cervical cancer cells was determined via a subcellular fractionation assay.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the working mechanism, lncRNAs can compete for miRNAs through the same miRNA recognition element, which lowers the negative regulatory actions of miRNAs on target genes and indirectly modulates target mRNA levels (33). To investigate whether USP30-AS1 acts as a miRNA sponge, the exact distribution of USP30-AS1 in cervical cancer cells was determined via a subcellular fractionation assay.…”
Section: Discussionmentioning
confidence: 99%
“…The important roles of lncRNAs in regulating physiological and pathological behaviours are achieved through various mechanisms. The lncRNA-mediated ceRNA theory is a classic mechanism that explains the mechanism of lncRNA action in EOC [12]. Cytoplasmic lncRNAs can act as endogenous molecular sponges to sequester certain miRNAs and indirectly modulate gene expression by protecting mRNAs from miRNA-induced mRNA deregulation or translation inhibition [33].…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, lncRNAs are con rmed to be crucial modulators of diverse physiological and pathological processes, especially during tumorigenesis and cancer progression [10]. An increasing amount of evidence has shown that an imbalance in lncRNA expression is closely correlated with the progression of EOC [11][12][13]. The dysregulation of lncRNAs has been clearly shown to exert cancer-inhibiting or cancer-facilitating effects and to contribute to the control of multiple aggressive properties of EOC [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Another epigenetic target to be considered is EZH2 because of its association with numerous ncRNAs. Indeed, EZH2 inhibition showed therapeutic efficacy against ovarian, colon and bladder cancers [175,250]. Tazemetostat, an EZH2 inhibitor, showed encouraging results in a phase 1 clinical trial for treating relapsed or refractory B-cell non-Hodgkin's lymphoma [251].…”
Section: Use Of Ncrnas In Clinical Therapymentioning
confidence: 99%